2017
DOI: 10.1055/s-0037-1607973
|View full text |Cite
|
Sign up to set email alerts
|

Search Engine Optimization: An Analysis of Rhinoplasty Web sites

Abstract: The Internet is the primary source of information for facial plastic surgery patients. Most patients only analyze information in the first 10 Web sites retrieved. The aim of this study was to determine factors critical for improving Web site traffic and search engine optimization. A Google search of “rhinoplasty” was performed in Michigan. The first 20 distinct Web sites originating from private sources were included. Private was defined as personal Web sites for private practice physicians. The Web sites were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…There is opportunity to optimize modern orthopedic websites to better integrate with Google's changing search algorithms to reach more patients. Search engine optimization techniques that have been widely employed by businesses are now also being used by medical practices to increase viewership [22,48,49]. As advances in information technology continue to shape our world, the field of orthopedics will need to adapt appropriately to best take care of our patients.…”
Section: Improving the Quality Of Online Health Informationmentioning
confidence: 99%
“…There is opportunity to optimize modern orthopedic websites to better integrate with Google's changing search algorithms to reach more patients. Search engine optimization techniques that have been widely employed by businesses are now also being used by medical practices to increase viewership [22,48,49]. As advances in information technology continue to shape our world, the field of orthopedics will need to adapt appropriately to best take care of our patients.…”
Section: Improving the Quality Of Online Health Informationmentioning
confidence: 99%
“…SEO specifically refers to improvement of what is known as “natural” or “organic” results which are unpaid results. Rayess et al [ 21 ] studied SEO in rhinoplasty websites. They state that most patients only analyse the results of the first ten websites retrieved.…”
Section: Discussionmentioning
confidence: 99%
“…Yudasubrata et al (2019) have shown that a positive correlation between information supply and demand has existed in the health field, but the performance of hospital websites is weakly correlated with the information demand. Rayess et al (2017) have expressed that, SEO is critical for facial plastic surgeons as it improves online presence.…”
Section: Introductionmentioning
confidence: 99%